2001
DOI: 10.1007/s11745-001-0759-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conjugated linoleic acid isomers on fatty acid profiles of liver and adipose tissues and their conversion to isomers of 16∶2 and 18∶3 conjugated fatty acids in rats

Abstract: Conjugated linoleic acid (CLA) is a collective term that describes different isomers of linoleic acid with conjugated double bonds. Although the main dietary isomer is 9cis,11trans-18:2, which is present in dairy products and ruminant fat, the biological effects of CLA generally have been studied using mixtures in which the 9cis,11trans- and the 10trans,12cis-18:2 were present at similar levels. In the present work, we have studied the impact of each isomer (9cis,11 trans- and 10trans,12cis-18:2) given separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
72
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 43 publications
18
72
3
Order By: Relevance
“…The preferential esterification of rumenic acid and its derivatives into polar lipids and oleic acid into neutral lipids confirmed previous results in the lamb liver showing that CLA and its conjugated derivatives such as C18:3, C20:3 and even C20:4 are mainly associated with polar lipids [18]. This preferential path of conjugated FA esterification appeared to be specific to ruminant animals since in the rat liver rumenic acid was mainly incorporated into neutral lipids [21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The preferential esterification of rumenic acid and its derivatives into polar lipids and oleic acid into neutral lipids confirmed previous results in the lamb liver showing that CLA and its conjugated derivatives such as C18:3, C20:3 and even C20:4 are mainly associated with polar lipids [18]. This preferential path of conjugated FA esterification appeared to be specific to ruminant animals since in the rat liver rumenic acid was mainly incorporated into neutral lipids [21].…”
Section: Discussionsupporting
confidence: 88%
“…The presence of these derivatives has been mentioned in the liver of different species such as the rat [16][17][18]21], lamb [19] and mouse [20]. Moreover, it has been recently demonstrated in the rat that the liver is able to convert rumenic acid into a conjugated derivative identified on the basis of its retention time as the cis-6, cis-9, trans-11 C18:3 [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipids, cholesteryl esters, and TG were separated by TLC on silica plates (Merck, Darmstadt, Germany). Their constitutive FAs were methylated according to the procedure of Christie, Sebedio, and Juaneda (16) and analyzed by gas-liquid chromatography as described previously (17). For skeletal muscle and heart, aliquots of total lipid extracts were resuspended in a solution of Triton X-100 as described previously (18).…”
Section: Lipid Analysismentioning
confidence: 99%
“…Park et al (1997) observed a reduction in the degree of obesity in mice given CLA. Namely, CLA promotes anabolic and suppresses catabolic processes, facilitates the incorporation of protein into muscle tissue, and reduces body fat accumulation in several animal models (DeLany and West, 2000;Pariza et al, 2000;Sebedio, 2001;Badinga et al, 2001).…”
mentioning
confidence: 99%